2020
DOI: 10.37107/jhas.175
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Depression among Elderly People Living In Old Aged Homes of Pokhara, Nepal

Abstract: Introduction: Depression is an important public health challenge in developing countries. Old people have a much higher risk of suicide then the general populations and are suffered from depression. In this context, this study aims to find the factors associated with depression among elderly people living in old aged homes in Pokhara. Methods: Three major elderly homes of Pokhara were selected purposively. Then information was collected from all the elderly people living in these old aged homes. Geriatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…82.6%. The above finding was in line with that of old-age home based cross-sectional study done in Nepal (80%), 4 and India(80%). 10 A similar study in Egypt showed a prevalence of 75%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…82.6%. The above finding was in line with that of old-age home based cross-sectional study done in Nepal (80%), 4 and India(80%). 10 A similar study in Egypt showed a prevalence of 75%.…”
Section: Discussionsupporting
confidence: 91%
“…3 Another similar study conducted in old-age homes in North India among 306 elderly revealed that 43.1% had some psychiatric illness with depression being the most common (53.7%). 4 The government of Nepal has declared the elderly citizens as people of age 60 years or more. 5 Like other developing countries, population ageing is a major public health concern in Nepal too.…”
Section: Introductionmentioning
confidence: 99%
“…In our study gender, education status wasn't statistically associated with depression while study done by Subedi et al found statistical association of gender (p=0.009) and education status (p=0.001 while Dhungana found statistical association of depression with gender (p=0.017). 14,21 Female were highly suffered from depression in both of the study. In the study done by Majdi et found 43.6% depression among male and 52.9% among female, study by Taqui et al found 15.7% depression among male 33% depression among female.…”
Section: Bivariate Analysismentioning
confidence: 79%
“…Another contradicts finding of study done by Dhungana found 80.7% of elderly people had depression. 21 This might be due to differences in the study settings; as it has been done in the old aged home where all the elderly people were away from their families. Another meta-analysis study done by Pilania et al showed aggregate prevalence of depression among elderly population about 34.4%.…”
Section: Bivariate Analysismentioning
confidence: 99%
“…However, in the developing country like Nepal and in the rural background settlements where transportation to health centers are not easily accessible, the decision to take for treatment also gets adversely affected. Dhungana (2020) found that a female living alone with low economic status is highly suffered from depression with respect to males. Joshi (2020) asserts that elderly people are often on stress in life due to some unfulfilled expectations, physical inability to involve in social activities, abuse, living arrangements, ignored condition in decision making in the family, household size, and property ownership.…”
Section: Introductionmentioning
confidence: 99%